A new Mittani Centre on the middle Tigris (Kurdistan region): report on the 2018 excavations at Kemune - Puljiz, Ivana; Qasim, Hasan Ahmed; Beutelschieß, Ralf; Faist, Betina (Zeitschrift für Orient-Archäologie, 2019)
In autumn 2018, the low water level of the Mosul Lake allowed rescue excavations to be carried out at the archaeological site of Kemune. The excavations revealed parts of a large building, probably a palace, dating to the Mittani period. Within the building, cuneiform tablets, seal impressions, remains of wall paintings and a huge amount of pottery were found. One cuneiform text indicates that Kemune was probably the ancient city of Zaḫiku.